2021
DOI: 10.1002/oby.23086
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Weight‐Reduced State: Physiology, Behavior, and Interventions

Abstract: Although many persons with obesity can lose weight by lifestyle (diet and physical activity) therapy, successful long‐term weight loss is difficult to achieve, and most people who lose weight regain their lost weight over time. The neurohormonal, physiological, and behavioral factors that promote weight recidivism are unclear and complex. The National Institute of Diabetes and Digestive and Kidney Diseases convened a workshop in June 2019, titled “The Physiology of the Weight‐Reduced State,” to explore the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 153 publications
2
47
0
1
Order By: Relevance
“…Our work supports these findings in that we have found that developing training and diet relationships and partners; increasing vegetables and fruits in the diet; spacing meals throughout the day; and, adding weekly counseling sessions, online diet and activity monitoring, and coaching feedback enhanced compliance and improved results [71,72]. Thus, as one counsel's individuals about effective weight loss strategies, the practitioner should attempt to incorporate some of these behavioral interventions [73,74].…”
Section: Behavioral Factors That Contribute Weight Loss and Maintenancesupporting
confidence: 68%
“…Our work supports these findings in that we have found that developing training and diet relationships and partners; increasing vegetables and fruits in the diet; spacing meals throughout the day; and, adding weekly counseling sessions, online diet and activity monitoring, and coaching feedback enhanced compliance and improved results [71,72]. Thus, as one counsel's individuals about effective weight loss strategies, the practitioner should attempt to incorporate some of these behavioral interventions [73,74].…”
Section: Behavioral Factors That Contribute Weight Loss and Maintenancesupporting
confidence: 68%
“…In the end, energy expenditure including caloric intake remain a key component of weight maintenance regardless of diet type 111 . Successful long-term weight loss is difficult to achieve and a workshop at the National Institute of Diabetes and Digestive and Kidney Diseases was held to discuss the physiology of the weight-reduced state 112 . The accumulation of data on key biological factors combined with behavioral, psychosocial, and environmental factors can help designing and delivering effective and tailored obesity treatments 113 .…”
Section: Possible Effects Of Adiposity On Global Warmingmentioning
confidence: 99%
“…The complex cascade of physiological factors involved in the regulation of energy balance (18) (19), which is large for a scalable intervention model. Similar weight losses were achieved in an analysis of a commercial implementation format (20).…”
Section: Prop Os Ed Re Vis I On Of Sc T In B Ehavior Al Interventions For Wei G Ht Manag Ementmentioning
confidence: 99%